Formulation of Biodegreaser Made from Palm Oil Methyl Ester Sulfonate Surfactant with Oxalic Acid Additive - Illah Sailah; Erliza Hambali; Fadilla Eka Aulyana (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2021)
The development of bio degreaser made from palm oil surfactant aims to substitute bio degreaser made from petroleum surfactant which is less environmentally friendly. The development was carried out by formulating palm methyl ester sulfonate (MES) surfactant with oxalic acid as metal or non-metal cleaning agent. The purpose of this study was to obtain the best concentration of oxalic acid in the bio degreaser formulation. The concentrations of oxalic acid tested were 7, 8, and 9%. The best concentration of oxalic acid was determined based on the results of characteristic tests and detergency tests, namely 7% oxalic acid concentration. The resulting bio degreaser product has a pH of 1.6; viscosity 1.39 cp; specific gravity of 1.012; surface tension 32 dyne/cm and detergency power 84%. Furthermore, the resulting bio degreaser was added with Diethanolamioda (DEA) surfactant. The purpose of adding DEA surfactant is to increase the pH and lower the surface tension. The formulation results showed an increase in pH from 1.6 to 3.2 and a decrease in surface tension from 31.97 dyne/cm to 28.70 dyne/cm. In addition, there was an increase in viscosity from 1.39 cp to 1.62 cp and specific gravity from 1.012 to 1.018.